2016
DOI: 10.1039/c6ob00430j
|View full text |Cite
|
Sign up to set email alerts
|

A surprising switch in absolute configuration of anti-inflammatory macrolactones

Abstract: Oxacyclododecindione-type macrolactones exhibit highly potent anti-inflammatory activities even at nanomolar concentration. After the determination of the relative configuration of the stereocenters at C14 and C15 by total synthesis of 4-dechloro-14-deoxyoxacyclododecindione and 14-deoxyoxacyclododecindione, the absolute configuration has now been assigned by X-ray crystallography. Surprisingly, the absolute configuration is (14S,15R) which differs for C15 from that of the well-known derivatives of (S)-curvula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 23 publications
3
14
0
Order By: Relevance
“…13−15 Because the triol system was the only hitherto unknown building block in this approach, the total synthesis began with its stereoselective preparation (Scheme 2). Starting from 1,3-propanediol (8), monoprotection with TBDPS-Cl, 16 followed by oxidation with 1-hydroxy-1,2-benziodoxol-3(1H)one-1-oxide (IBX), 17 produced a suitable precursor 9 for an asymmetric Evans syn-aldol reaction in two steps and 84% overall yield (for full stepwise details; see Supporting Information Scheme S1). Aldehyde 9 was then subjected to typical Evans aldol conditions using the chiral oxazolidinone 10, which led to the formation of the syn-aldol product with an 88% yield.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13−15 Because the triol system was the only hitherto unknown building block in this approach, the total synthesis began with its stereoselective preparation (Scheme 2). Starting from 1,3-propanediol (8), monoprotection with TBDPS-Cl, 16 followed by oxidation with 1-hydroxy-1,2-benziodoxol-3(1H)one-1-oxide (IBX), 17 produced a suitable precursor 9 for an asymmetric Evans syn-aldol reaction in two steps and 84% overall yield (for full stepwise details; see Supporting Information Scheme S1). Aldehyde 9 was then subjected to typical Evans aldol conditions using the chiral oxazolidinone 10, which led to the formation of the syn-aldol product with an 88% yield.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Our contributions to the area of this macrolactone family include total syntheses, structure elucidation, and derivatizations and the establishment of initial structure–activity relationships through bioassays. , However, despite several attempts, it has not yet been possible to prepare a macrolactone possessing a hydroxylated aliphatic backbone, as found in natural products 1 and 4 . Fermentation of the producing strains provided only very small quantities of the hydroxylated derivatives oxacyclododecindione ( 1 ) and 13-hydroxy-14-deoxyoxacyclododecindione ( 4 ), , and the synthesis of the proposed natural product 4 reported herein is the first of its kind.…”
mentioning
confidence: 99%
“…1 H and 13 C NMR spectra of both synthetic (14S,15R)-2 and (14S,15R)-3 were in good agreement with the data of the natural products. 8…”
Section: Resultsmentioning
confidence: 99%
“…Soon aer, the absolute conguration of natural 2 and 3 was determined as (14S,15R) by X-ray crystallography. 8 To date, the asymmetric synthesis of natural macrolactones 2 and 3 is still an untouched work.…”
Section: Introductionmentioning
confidence: 99%
“…At present, this family comprises oxacyclo­dodecindione ( 1 ), 4-dechloro-14-deoxyoxacyclo­dodecindione ( 2 ), 14-deoxyoxacyclo­dodecindione ( 3 ), and the recently reported 13-hydroxy-14-deoxyoxacyclo­dodecindione ( 4 ) (Scheme ). Isolated from the imperfect fungus Exserohilum rostratum , these secondary metabolites ( 1 – 4 ) exhibit remarkable anti-inflammatory and antifibrotic properties, positioning them as a promising starting point for the development of drugs against chronic inflammation and fibrotic diseases like asthma, rheumatoid arthritis, and systemic lupus erythematosus or neoplastic diseases. ,, Prior research on these 12-membered macrolactones, including total syntheses, derivatization studies, and the establishment of initial structure–activity relationships through bioassays, has identified the enone moiety and the monochlorinated resorcinol backbone as crucial for their bioactivity, limiting the opportunities for modifications in these regions of the molecule. To further investigate the potential of this compound family, current investigations consequently focus on the aliphatic backbone, to which molecular handles might be attached to facilitate the ongoing search for their biological target(s), which are still unknown at present. Our total synthesis of the proposed natural product 4 , isolated in 2018 by Shang and Lin et al, revealed mismatching spectroscopic data and required a reassignment of the initially proposed configuration .…”
mentioning
confidence: 99%